2020
DOI: 10.1016/j.ajoc.2020.100900
|View full text |Cite
|
Sign up to set email alerts
|

Heads up Sutureless Chandelier assisted scleral buckle

Abstract: Purpose This study aims to describe chandelier assisted scleral buckle (CSB) using 3D visualizing system in phakic uncomplicated Rhegmatogenous Retinal Detachment (RRD). Methods This technique was performed in 6 eyes of 6 patients with primary rhegmatogenous RD who underwent encircling circumferential scleral buckling with scleral tunnels. Heads up display 3D system was used for visualization and localization of the breaks, and Chandelier Endoillumination was used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(20 reference statements)
0
4
0
Order By: Relevance
“… 6 7 For this reason, clinical studies investigating the results of improved vitreoretinal illumination and visualization techniques in scleral buckle surgery with wide-angled visualization, heads-up surgery, and 3D visualization platforms have become more popular. 9 10 This study also contributes to the literature reporting the outcomes of wide-angled visualization with chandelier endo-illumination method in scleral buckle surgery.…”
Section: Discussionmentioning
confidence: 73%
“… 6 7 For this reason, clinical studies investigating the results of improved vitreoretinal illumination and visualization techniques in scleral buckle surgery with wide-angled visualization, heads-up surgery, and 3D visualization platforms have become more popular. 9 10 This study also contributes to the literature reporting the outcomes of wide-angled visualization with chandelier endo-illumination method in scleral buckle surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Scleral belt loop tunnels are becoming increasingly popular for securing the encircling band to the sclera. [4][5][6][7] Spontaneous dehiscence of scleral loop tunnels is rare. Fukumoto et al 8 reported a patient who presented with mild foreign body sensation and visible silicone band under the conjunctiva one year after a combined pars plana vitrectomy and SB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The method has recently gained popularity as more SB procedures are performed under microscopy, as a "sutureless" surgery, or using 3D visualization systems. [4][5][6][7] In this method, the encircling buckle material is anchored to sclera through a partial thickness circumferential scleral tunnel that is usually dissected using a crescent knife. Globe perforation through full-thickness None of the authors has any financial/conflicting interests to disclose.…”
mentioning
confidence: 99%
“…Since then, several studies have examined the efficacy of chandelier-assisted scleral buckling surgery, with some studies also comparing it to standard scleral buckling. 2,5,6,8,1035 The advent of chandelier scleral buckling has helped improve the identification of retinal breaks that may have been previously missed in the preoperative examination when performing standard scleral buckling. 6 Chandelier scleral buckling also has the added benefit of potentially improving visualization in pseudophakic eyes.…”
Section: Introductionmentioning
confidence: 99%